Photoisomerization in Photoaligned Azo Dyes Exhibiting Photostability - Hegde, Gurumurthy; Kozenkov, V. M.; Chigrinov, V. G.; Kwok, H. S. (Taylor & Francis, 2009)
Two new light scattering modes have been discovered in short helix pitch (p0ﬃ350 nm) ferroelectric liquid crystal (FLC). One of the modes arises because of a special kind of the FLC structure non-uniformity that originates inherently as a new phenomenon if the helix pitch is very small. Another mode relates to the helix twisting after the driving voltage switching off.